The Role of Online Reviews and Trust in the Adoption of E-Commerce for Online Vestment Transactions - Sahu, Premendra; Bakshi, Shailja; Sharma, Menka; Dholkia, Nikita; Bhargav, Sindura; Pattanayak, Suresh Kumar; Rathi, Suchitra (International Review of Management and Marketing, 2024)
In the contemporary era, the advent of online shopping has revolutionized consumer behavior, particularly in the domain of vestment purchases, by elucidating the mechanisms through which online reviews shape individual buying behavior. This study delves into the impact of online reviews on individual buying behavior in the context of vestment shopping. Leveraging the Kaiser-Meyer-Olkin (KMO) measure, alongside a sample size of 374 participants, this research examines the significance of online reviews in shaping consumer decisions. The findings of this study underscore the significant impact of online reviews on consumer decision-making processes in the realm of vestment shopping. Participants consistently cited online reviews as influential factors in their purchasing decisions, with positive reviews exerting a particularly strong influence on their likelihood of making a purchase. Moreover, factors such as credibility, relevance, specificity, and sentiment of reviews emerged as critical determinants shaping consumer perceptions and preferences. Study has provided valuable insights into the influence of online reviews on individual buying behavior in the context of online vestment shopping through the application of the Kaiser-Meyer-Olkin (KMO) tool and analysis of a sample size comprising 374 responses and illuminating the intricate dynamics at play within this niche market segment.